The Relationship Between Parent Parenting And Development On Toddler (1-5 Years) In Lukhu Lase Village East Lahewa Sub-District In 2022 - Dina Hura; Hetty Mulyani Lase; Purnamasari Nazara (International Journal of Health Engineering and Technology, 2024)
The pattern of parenting in the first five years of a child's life is very influential on four developmental domains namely motor, cognitive, language, and social emotional of the child. These aspects are very influential on children's development and behavior in the future. Research purposes. To find out the relationship between parenting and development in toddlers (1-5 years). Research design. Using observational analytic methods with cross sectional design. Sample. A total of 62 respondents with accidental sampling technique. Instrument. The parenting questionnaire and the developmental screening questionnaire (KPSP) were used. Data analysis was done by univariate and bivariate analysis. Results. The majority of parents adopted democratic parenting as much as 23 (37.1%), the minority adopted authoritarian parenting as much as 19 (30.6%) and the majority of children under development doubted as many as 23 (37.1%), minority deviant developmental toddlers 17 (27.4%). Conclusion. There is a relationship between parenting style and development in toddlers (1-5 years) in Lukhu Lase Village, East Lahewa Sub-district, the value of p = 0.001 <= 0.05. Suggestion. It is expected that parents provide the best care for their children because the first five years of age the child will determine its character going forward.